Clinical Psychology Services for Patients Hospitalized Due to COVID-19 During the Pandemic in Northern Italy: From Isolation to Rehabilitation - Callus, Edward; Bertoldo, Enrico Giuseppe; Fiolo, Valentina; Pagliuca, Silvana; Baroni, Barbara (Frontiers in Psychology, 2021)
The objective of this paper is to describe the organization and modality of provision of clinical psychology services for those patients who had to be hospitalisedhospitalized due to COVID-19 during the pandemic in Northern Italy. The IRCCS Policlinico San Donato hospital in Milan, was converted into a COVID-19 center in March 2020, and all the staff, including the Clinical Psychology Service Team, were diverted to assist these patients. A description is given of how the service was organisedorganized and the modalities which were utilisedutilized to assist the patients. Following the pertinent ministerial decrees, guidelines and relevant literature, the patients were followed-up through telehealth (via phone, smartphone, or tablet with audio or audio-visual calls). A COVID-19 rehabilitation unit was later opened in April 2020, where all patients were seen and followed-up by the Clinical Psychology team, the last patient being discharged at the end of June. Details are given about the type of services provided during the hospitalization at the different points in time. At admittance and subsequent isolation, patients indicated by the medical and nursing staff, and those who specifically requested it, were given psychological support. Patients transferred to the COVID-19 rehabilitation unit were all evaluated for anxiety, depression, post-traumatic stress disorder and sleep disorders both on admission and at discharge when possible.